Traditional and environmentally preferable cleaning product exposure and health symptoms in custodians. Issue 9 (4th June 2015) - Garza, Jennifer L.; Cavallari, Jennifer M.; Wakai, Sara; Schenck, Paula; Simcox, Nancy; Morse, Tim; Meyer, John D.; Cherniack, Martin
<x xml:space="preserve">Abstract</x> Background We investigated the associations between traditional and environmentally preferable cleaning product exposure and dermal, respiratory, and musculoskeletal symptoms in a population of custodians. Methods We analyzed associations between symptoms and exposure to traditional and environmentally preferable cleaning product exposure among 329 custodians. Results We observed increased odds of dermal (P < 0.01), upper (P = 0.01) and lower respiratory (P = 0.01), and upper extremity (P < 0.01), back (P < 0.01), and lower extremity (P = 0.01) musculoskeletal symptoms associated with increased typical traditional cleaning product exposure. We observed significant trends for increased odds of dermal (P = 0.03) and back (P = 0.04) and lower (P = 0.02) extremity musculoskeletal symptoms associated with increased typical environmentally preferable cleaning product exposure. Conclusions Fewer positive associations and reduced odds of health symptoms associated with environmentally preferable cleaning product exposure suggest that these products may represent a safer alternative to traditional cleaning products. Am. J. Ind. Med. 58:988–995, 2015. © 2015 The Authors. American Journal of Industrial Medicine Published by Wiley Periodicals, Inc.